THE EFFECT OF INFLATION, INTEREST RATE, EXCHANGE RATE AND GROSS DOMESTIC PRODUCT GROWTH ON COMPOSITE STOCK PRICE INDEX (Study at Indonesia Stock Exchange Period of 2010-2019) - Tampubolon, Kristanty Monica; H. M. Roy Sembel; Sidharta, Juaniva (Universitas Kristen Indonesia, 2021)
The purpose of this study is to determine the effect of inflation, interest rate, exchange rate, and gross domestic product growth on composite stock price index. The research design used in this study is multiple linear regression. Pearson correlation test, F-test and t-test are used in hypotesis testing. To have a more reliable result, these data undergone several tests, which are descriptive statistics, boxplot statistics, normality, heteroscedasticity, multicollinearity, and autocorrelation. The results of this study showed that exchange rate and gross domestic product growth significantly affect composite stock price index. Inflation and interest rate were insignificant in explaining composite stock price index. Coefficient of determination is 37.2%. It shows that 37.2% variation of dependent variable can explained by variation of four independent variables in this research, while the rest of 62.8% explained by the other variables which are not scrutinized in this study. Keywords:composite stock price index, inflation, interest rate, exchange rate, growth gross domestic product.